JURGEN HABERMAS AND HIS CONTRIBUTION TO THE THEORY OF DELIBERATIVE DEMOCRACY - Jovanoski, Aleksandar; Sharlamanov, Kire (American International Journal of Social Science Research, 2021)
The paper presents Jürgen Habermas' epistemological views on the theory of deliberative democracy. Habermas has been constructing a series of assumptions since the 1970ies about his Theory of Communicative Action to overcome the crisis of legitimacy. This position stems from the critique of the deep chasm that exists between the "constitutional-democratic legal order" as a normative framework and how forms of social power are imposed to undermine the legitimate process of passing laws. The course of Habermas's argumentation theorizing about communicative action and the communicatively based process of (democratic) political decision-making brings with it the potential to break with the procedural argumentation of the representatives of the so-called aggregate models of democratic practice. For the development of the theory of deliberative democracy, its sociological sharpness may be important, with the help of which the social basis of legal projects and public policies leads to the clarification of the external tension that exists between facticity and validity. Thus, Habermas respects the differences between facts and norms in every contemporary concept of law. This can be called the legal theory of deliberative democracy that has shaped the modern understanding of the conception and practice of deliberative democracy.